9 - Digital Technologies and Election Management in Zimbabwe: Pseudo-democratic Transition and Contorted Delirium? - Mude, Torque (Africa Development, 2022)
This article examines the extent to which the adoption of biometric voter registration in election management in Zimbabwe has appeared a phantom on the horizon regarding democratisation. While the emergence of digitalised election management brought with it expectations of credible electoral processes and outcomes in a country with a history of rampant electoral malpractices in manually managed processes, the phenomenon is yet to yield positive results regarding democratisation in Zimbabwe. Despite the shift from manually managed electoral process to a digitalised approach, the quagmire of irregularities has persisted in Zimbabwean elections. This is largely attributable to the trajectory of governance in Zimbabwe which appears to militate against the exploitation of the opportunities presented by digital technologies in democratising elections in the county. This said, the conclusion drawn from this article is that the configuration of political power, particularly issues of the breach of the democratic principles of separation of power and separation of personnel, are disingenuous to technology-induced democratic transition to credible elections. Secondary research was used to obtain data for this article as data were gathered from books, journal articles, newspaper articles and institutional reports